Three-year stability of posterior corneal elevation after small incision lenticule extraction (SMILE) for moderate and high myopia - Zhao, Yu; Knorz, Michael C. (Journal of refractive surgery, 2017)
Journal of Refractive Surgery | PURPOSE:To investigate long-term changes in posterior corneal elevation after small incision lenticule extraction (SMILE).METHODS:Thirty-six eyes of 20 patients (7 male, 13 female) who underwent SMILE were recruited for this prospective consecutive study. The mean preoperative manifest spherical equivalent was −6.24 ± 1.47 diopters (D) (range: −3.88 to −8.75 D). Posterior corneal surfaces were